Research progress on biot-mercury interactions in the periphyton: environmental processes, ecological effects and restoration applications - Li, Pan; Xu, Ming; Xu, Yufeng; Zhao, Wenyu; Miao, Luyao; Zhou, Jie (Frontiers in Environmental Science, 2026)
Mercury (Hg) is a pervasive global pollutant whose environmental impact is critically defined by its speciation. This review synthesizes data from 100 studies to quantify the central role of periphyton, a ubiquitous microbial-algal biofilm, in Hg sequestration and transformation. Analyses show that periphyton extracellular polymeric substances (EPS), rich in carboxyl, hydroxyl, and sulfhydryl groups, achieve rapid Hg(II) biosorption within milliseconds, with reported adsorption capacities ranging widely from 27.2 mg/g for fungal components to over 393 mg/g for specific bacterial strains. Simultaneously, the anaerobic microzones of periphyton serve as biochemical reactors where microbial guilds (e.g., sulfate-reducing bacteria and methanogens) mediate methylation via the hgcAB gene cluster and demethylation via the mer operon. A key finding consolidated from the literature is that upon senescence, this mercury-laden biomass can enhance sediment methylmercury (MeHg) concentrations by 54%–514%, creating bioaccumulation hotspots. This review systematically dissects the adsorption mechanisms, environmental drivers, physiological adaptations, and bioremediation applications, highlighting that periphyton’s dual function as a sink and source of MeHg is a pivotal, yet underexplored, dynamic in Hg cycling. We conclude by emphasizing the urgent need to couple micro-scale mechanistic understanding with watershed-level models and to develop in situ monitoring and targated regulation strategies.